2015
DOI: 10.1007/s12035-015-9120-7
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Gene 5-HTTLPR Polymorphism as a Protective Factor Against the Progression of Post-Stroke Depression

Abstract: Polymorphisms in the 5-HTT and BDNF genes are shown to affect their function at the molecular and serum level. Prior work has tried to correlate the polymorphisms with post-stroke depression (PSD), the results nevertheless remain indefinitive. A plausible reason accounting for the uncertainty relates to the small sample of each published trial. In this study, we have performed a comprehensive meta-analysis in order to evaluate the effects of 5-HTT and BDNF polymorphisms (5-HTTLPR, STin2 VNTR, 5-HTR2a 102 T/C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The elevation of IL-6 in patients that have strokes could possibly predict the development of poststroke depression [23,24]. In another meta-analysis, brain-derived neurotrophic factor (BDNF) was found to be involved in the development of depression and poststroke depression [25,26]. In these studies, a low serum level of BDNF in the acute phase after a stroke was associated with the development of poststroke depression.…”
Section: Biomarkers Associated With Poststroke Depressionmentioning
confidence: 99%
See 4 more Smart Citations
“…The elevation of IL-6 in patients that have strokes could possibly predict the development of poststroke depression [23,24]. In another meta-analysis, brain-derived neurotrophic factor (BDNF) was found to be involved in the development of depression and poststroke depression [25,26]. In these studies, a low serum level of BDNF in the acute phase after a stroke was associated with the development of poststroke depression.…”
Section: Biomarkers Associated With Poststroke Depressionmentioning
confidence: 99%
“…BDNF is inherently involved in hippocampal plasticity and memory [27]. One study found a significant negative relationship between BDNF and NIHSS [25][26][27]. In rodent models, low levels of BDNF in the hippocampus that had an acute stroke exhibited depressed behavior, however if BDNF was overexpressed there was a marked decrease in depressed behavior [21].…”
Section: Biomarkers Associated With Poststroke Depressionmentioning
confidence: 99%
See 3 more Smart Citations